Learning Management in Police Academy Educational Institutes and Training - Widada, T; Slamet, A; Sumaryanto Florentinus, T; Martono, S (KnE Social Sciences, 2018)
Learning management in Police Academy Educational Institutes and Training covers planning, implementing, evaluating, and controlling. Learning management is done by Educators in order to achieve high qualified graduates in Police Academy Educational Institute and Training. Besides that, it indirectly improves Educators’ competence. However, there are some teachers that use monotonous lecturing as their learning method on the planning stages. The effect is the students feel less concentration during learning process. This research is done by using descriptive approach to solve the problem. Variables of the research are management, learning, and learning management. It uses primary and secondary data to obtain the information. The primary data were obtained through interview and observation, and the secondary data were obtained from written sources through documentation that is related to learning management in Police Academy Educational Institutes and Training. Technique analysis of the data is descriptive qualitative. The results of this study show that learning management done by teachers covers planning, implementing, evaluating, and controlling. The lesson plan composed by teachers still use monotonous lecturing as learning method on the planning stages in each meeting. Keywords: management, learning, learning management